Angulated versus parallel headless cannulated screw fixation for type 1 capitellum fracture: A finite element study - Bulent Alp, Nazmi; Efendigil, Tugba; Demir, Ozgur; Bilsel, Kerem; Can Kalay, Onur; Karpat, Fatih (Annals of Medical Research, 2021)
Aim: The unique shape and vascularization make capitellar fractures challenging to treat. In such cases, screw inclination is crucial to achieve stable fixation. In the present study, we aimed to evaluate the mechanical outcome of the different fixation angles formed by headless cannulated screws for treatment of type 1 capitellum fracture and compared interfragmentary displacement (IFD) using finite element analysis (FEA). Material and Methods: In our study, three-dimensional finite element stress analysis was applied using the isotropic materials and static linear analysis. Stochastic screw inclination scenarios (Case 1, Case 2, Case 3, and Case 4) were generated, and perpendicular application of loads were simulated with magnitudes between 50 and 300 N on the elbow at angulations from 0º to 145º. The IFD in the four different screw inclination pairs were listed in the ANSYS general end processor. Relative IFD was calculated by measuring the total displacements in the X/Y/Z planes from 16 different points.Results: According to the modeling, the magnitude of IFD was significantly different in terms of the force and the case factors under four altered forces. Analysis of displacement exhibited a significant difference in the force values of ‘100N/200N/300N’ and in the screw inclinations of Case 2 only. Although the interaction effect between the Force*Case was observed to be low, the most noticeable results were obtained from the “300N*Case 2.” pair compared to the others (p0.05).Conclusion: Screws used for fracture fixation must maintain an anatomical correction, until it heals. Following a complex trauma such as a capitellar fracture, the elbow joint needs a stable fixation and early mobilization. Our FEA results suggest that the fixation via angled screws can achieve a more stable configuration than the paralleled ones.
Keywords: Finite element analysis; headless cannulated screws; interfragmentary displacement; Type 1 capitellum fracture